SiOx nanoparticle fabrication and applications - Lim, Xian Yang (2019)
Silica nanospheres are widely researched not just for its synthesis mechanism but also its applications, especially mesoporous silica nanospheres. In this Thesis, we study the synthesis of non-porous silica nanospheres by using Stöber’s process by manipulating the concentration of the reagents (TEOS) and the type of alcohol used. We also propose a method of dispersing the nanospheres on silicon wafers and attempt to deposit Titanium and Nickel layers on the silicon wafers with nanospheres for the application as an electronic getter.